2021
DOI: 10.1002/cam4.3707
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre clinicopathological study of adenoid cystic carcinoma: A report of 296 cases

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
12
1
4
Order By: Relevance
“…5 Moreover, another study of 51 patients with ACC of the nasal cavity and paranasal sinuses reported that CK8/18, CK5/6, CD117, SMA, and S100 were expressed in 100%, 100%, 94.1%, 88.3%, and 66.3% of lesions, respectively. 12 In the present case, the initial immunohistochemical findings were CK5/6 (few þ) and p63 (few þ), leading to a diagnosis of nonkeratinizing NPC. However, after 7 months, the second histopathological analysis revealed negativity for CK5/6 and p63, which excluded a squamous cell origin, and positivity for MOC31 and Ber-EP4, suggesting a glandular cell origin, which resulted in a final diagnosis of NAC.…”
Section: Discussionmentioning
confidence: 57%
“…5 Moreover, another study of 51 patients with ACC of the nasal cavity and paranasal sinuses reported that CK8/18, CK5/6, CD117, SMA, and S100 were expressed in 100%, 100%, 94.1%, 88.3%, and 66.3% of lesions, respectively. 12 In the present case, the initial immunohistochemical findings were CK5/6 (few þ) and p63 (few þ), leading to a diagnosis of nonkeratinizing NPC. However, after 7 months, the second histopathological analysis revealed negativity for CK5/6 and p63, which excluded a squamous cell origin, and positivity for MOC31 and Ber-EP4, suggesting a glandular cell origin, which resulted in a final diagnosis of NAC.…”
Section: Discussionmentioning
confidence: 57%
“…All these subtypes can be identified based on the dominant shape and arrangement of the epithelial secreting cells, the myoepithelial cells, and the extracellular matrix. There is no proper protocol to distinguish between these subtypes, but a recent study has suggested that the histologic subtype can be considered to be solid when the solid pattern accounts for more than 30% of the tumor [ 71 ]. A retrospective study of 87 SACC cases indicated that the cribriform subtype was the most encountered histologic pattern of SACC and that the solid was the least common [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 Previous studies with a relatively large number of patients have mainly focused on the pathology, immunohistochemical characteristics, treatment, and prognosis of ACC. [12][13][14] The imaging characteristics of salivary gland ACC have not been well described, and most imaging studies have been small series or case reports. 9,15,16 To the best of our knowledge, this is the first study to describe the clinical and US characteristics of ACC in the major salivary glands.…”
Section: Discussionmentioning
confidence: 99%